Lysianopsis adelae, new species of amphipod (Gammaridea: Lysianassidae) from the Veracruz Coral Reef System, SW Gulf of Mexico - Winfield, Ignacio; Ortiz, Manuel (Zootaxa, 2009)
A new species of amphipod of the genus Lysianopsis from the Veracruz Coral Reef System, SW Gulf of Mexico is described. Lysianopsis adelae n. sp., was collected in the sediments at the base of the sponge Aplysina fistularis at a depth of 10 m. The differences among L. alba, L. hummelincki, and L. ozona, recorded from Gulf of Mexico and Caribbean Sea are pointed out and they are compared with the new species.